The Presence or Absence of Mole in Mexican Fiestas - Adapon, Joy (Petits Propos Culinaires, 2001)
The author looks at the role of mole in Mexican feasts which, as a dish requiring skill, expense and time to prepare, seems to be always represented at important occasions even when economic conditions dictate that a proxy is needed since it is the tradition of serving mole that counts.